Ethnic Inclusiveness of the Central State Government and Economic Growth in Sub-Saharan Africa. (15th February 2019) - Gaspart, Frédéric; Pecher, Pierre
Abstract: We estimate the effect of the share of ethnic groups included in the central government on economic growth, distinguishing between democracies and autocracies in a panel of 41 Sub-Saharan African countries over the period from independence to 1999. We exploit evidence from the Ethnic Power Relations database, which categorises the politically relevant ethnic groups regarding access to state power. We take advantage of the time variation of political participation, using Fixed-Effects and Difference-GMM estimations. Our dynamic-panel growth models display a robust positive effect of the proportion of included groups in democracies. Such an effect is offset in autocracies, and the difference is often significant. This finding withstands the introduction of various controls, outlier tests, and specification checks. Our results support the view that institutional improvements must accompany the promotion of inclusiveness in low-income and weakly-institutionalised countries.